New international federation of gynecology and obstetrics (FIGO) staging classification for cancer of the ovary, fallopian tube, and peritoneum: Nova klasifikacija raka jajčnikov, jajcevodov in peritoneja mednarodnega združenja ginekologov in porodničarjev (FIGO) - Arko, Darja; Gajser, Verena; Takač, Iztok (Acta Medico-Biotechnica, 2021)
The new staging system for cancer of the ovary, fallopian tube, and peritoneum (last revision, 1988) was approved under the auspices of the International Federation of Gynaecology and Obstetrics (FIGO) in 2012. Previously, peritoneal cancer did not have a staging system. The new classification has been valid since January 2014.New findings and a more complete understanding of the molecular pathogenesis underlying ovarian cancer, combined with scientific discoveries identifying prognostic factors have led to changes in the new FIGO classification system. Based on the same symptomatology, treatment, and prognosis, it was established that a lot of similarities are shared between ovarian cancer, primary fallopian tube cancer, and primary peritoneal cancer.
Keywords: staging system; cancer; ovary; fallopian tube; peritoneal